2021
DOI: 10.1536/ihj.20-619
|View full text |Cite
|
Sign up to set email alerts
|

MiR-518a-5p Targets GZMB to Extenuate Vascular Endothelial Cell Injury Induced by Hypoxia-Reoxygenation and Thereby Improves Myocardial Ischemia

Abstract: To probe the function of miR-518a-5p/Granzyme B (GZMB) in hypoxia/reoxygenation (H/R)-induced vascular endothelial cell injury.The key genes of myocardial infarction were screened by bioinformatic methods. The upstream micro RNAs (miRNAs) of GZMB were predicted by TargetScan. The binding of miR-518a-5p to GZMB was verified with luciferase reporter assay. The H/R model was constructed with human vascular endothelial cell (HUVEC) in vitro. Cell Counting Kit-8 (CCK8) assay was performed to detect cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Other miRNAs that suppress apoptosis in cardiomyocytes are miR-431, 518a-5p, and miR-105, by targeting autophagy-relate 3 (ATG3), Granzyme B (GZMB), RIP3, and BNIP3 respectively. 29,41,47 The downregulation of miR-431, miR-518, and miR-105 in Young AMI against Mature AMI patients in our study, suggest that age factor may lead to differential expression of these miRNAs.…”
Section: Discussionmentioning
confidence: 49%
“…Other miRNAs that suppress apoptosis in cardiomyocytes are miR-431, 518a-5p, and miR-105, by targeting autophagy-relate 3 (ATG3), Granzyme B (GZMB), RIP3, and BNIP3 respectively. 29,41,47 The downregulation of miR-431, miR-518, and miR-105 in Young AMI against Mature AMI patients in our study, suggest that age factor may lead to differential expression of these miRNAs.…”
Section: Discussionmentioning
confidence: 49%
“…Granase B (GZMB), a member of the serine protease family of granase, promotes apoptosis and is currently the most widely studied granase in the eld of health and disease [46]. Studies have shown that mir-518a-5p can target GZMB to reduce hypoxia-reoxygenation-induced vascular endothelial cell injury, thereby improving coronary artery disease [47]. GZMK, belonging to the granase serine protein family, also plays a key role in myocardial ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-124 induces ECs apoptosis via the P38/MAPK and PI3K/AKT pathways and may be a contributing factor in vascular endothelial damage in AMI [ 43 ]. By targeting granzyme B, MiR-518a-5p can reduce hypoxia/reoxygenation (H/R)-induced apoptosis and cell damage in human umbilical vein endothelial cells (HUVECs) [ 44 ].…”
Section: Apoptosismentioning
confidence: 99%